Perancangan Desain UI/UX Aplikasi Slow Living dengan Design Thinking - Rafansya, Muhammad Ramadzikri; Suranto, Beni (AI Society & STMIK Indonesia, 2024)
In today’s fast-paced urban environments, stress and mental fatigue are increasingly prevalent due to demanding routines and high productivity expectations. In response, the concept of slow living has gained traction as an alternative lifestyle, promoting mindfulness, balance, and well-being—especially following the COVID-19 pandemic, which heightened the need for mental and physical health prioritization. This study presents the design and development of a UI and UX for a slow living mobile application, employing the Design Thinking framework, which includes five iterative stages: empathize, define, ideate, prototype, and test. This user-centered approach aligns with the slow living philosophy by prioritizing simplicity, ease of use, and aesthetic appeal. The application aims to assist individuals in achieving equilibrium amidst in a fast-paced lifestyle. Evaluation of the app yielded a high System Usability Scale (SUS) score of 90.83, demonstrating strong user acceptance and confirming that the experience resonates with the principles of slow living.